2011
DOI: 10.1007/978-1-4614-0106-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish: Model for the Study of Inflammation and the Innate Immune Response to Infectious Diseases

Abstract: The zebrafish (Danio rerio) has been extensively used in biomedical research as a model to study vertebrate development and hematopoiesis and recently, it has been adopted into varied fields including immunology. After fertilization, larvae survive with only the innate immune responses because adaptive immune system is morphologically and functionally mature only after 4-6 weeks postfertilization. This temporal separation provides a suitable system to study the vertebrate innate immune response in vivo, indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
173
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(175 citation statements)
references
References 141 publications
(152 reference statements)
2
173
0
Order By: Relevance
“…[50][51][52][53][54][55] The up-modulated ADP-ribosylation factor GTPase activating protein 1 (ARF-GAP1) also seems to significantly modify the transport of G protein-coupled receptors, 56 including chemokine (C-X-C motif) receptor 4 (CXCR4), which has been related to TLR4 and LPS tolerance. 13,57 This response was also observed in the enrichment of GO terms in the comparison SLD-treated fish against controls (Supplementary Table S4). …”
Section: Dios Et Almentioning
confidence: 59%
“…[50][51][52][53][54][55] The up-modulated ADP-ribosylation factor GTPase activating protein 1 (ARF-GAP1) also seems to significantly modify the transport of G protein-coupled receptors, 56 including chemokine (C-X-C motif) receptor 4 (CXCR4), which has been related to TLR4 and LPS tolerance. 13,57 This response was also observed in the enrichment of GO terms in the comparison SLD-treated fish against controls (Supplementary Table S4). …”
Section: Dios Et Almentioning
confidence: 59%
“…In this period, the embryo solely relies on the innate immune system ( Fig. 1) (van der Sar et al 2004b;Meeker and Trede 2008;Novoa and Figueras 2012;van der Vaart et al 2012), which provides the opportunity to study the contribution of innate immunity to disease in an isolated fashion. Furthermore, it allows for distinguishing between this arm of immunity and a combined innate and adaptive immune response in the context of infection, like in adult fish, which have a complex adaptive immune system akin to that of mammals ( Fig.…”
Section: General Properties Of Zebrafishmentioning
confidence: 99%
“…Zebrafish embryos and adult forms are already emerging as a powerful tool to study inflammation due to remarkable similarity of its immune mechanism with the human immune system. [27][28][29] The major components of the immune recognition system and defense signaling pathways are conserved between fish and mammals. In this regard, it has been shown that 48 h postfertilization, zebrafish embryos develop innate immunity with the activation of macrophages and neutrophils, while adaptive immunity is functional after 4 days postfertilization.…”
Section: Viral Infection In Zebrafish and Inflammationmentioning
confidence: 99%
“…The optical clarity in zebrafish embryos together with the expression of viral entry receptors (Fig. 1), 11 and a well-developed immune system [28][29][30] as well as evolutionarily conserved host defense strategies 27,35 make zebrafish an excellent model to study multiple events of viral pathogenesis.…”
Section: Zebrafish Model: Overall Advantages To Study Viral Infectionsmentioning
confidence: 99%